Effects of nutrient solution irrigation quantity and powdery mildew infection on the growth and physiological parameters of greenhouse cucumbers - Mao, Hanping; Wang, Yafei; Yang, Ning; Liu, Yong; Zhang, Xiaodong (International Journal of Agricultural and Biological Engineering, 2022)
For important economic crops such as cucumbers, abiotic and biotic stress conditions have had an adverse effect. This study aimed to observe the effects of water stress and powdery mildew stress on cucumber plants. Biotic stress at two levels, B0 (no powdery mildew stress) and B1 (powdery mildew stress) with three fertigation requirement levels (T1: Full fertigation, T2: Moderate nutrient solution deficit, T3: Severe nutrient solution deficit). Therefore, set up six treatments of B0T1, B1T2, B0T3, B1T1, B1T2, and B1T3. Leaf gas-exchange parameter first decreases and then increases under B1T1, B1T2, and B1T2. The leaf gas exchange parameter was significantly decreased under B0T2 and B0T3. Compared to the control experiment (CK, B0T1: no disease infestation and full irrigation), the plant height of cucumber decreased by 7.55%, 10.62%, 15.28%, 23.27%, and 35.16%, respectively, under B0T2, B0T3, B1T1, B1T2 and B1T3; the stem diameter of cucumber decreased by 9.46%, 15.74%, 5.47%, 13.45%, and 23.72%, respectively, under B0T2, B0T3, B1T1, B1T2, and B1T3; the leaf area of cucumber decreased by 13.76%, 29.96%, 13.43%, 38.21%, and 66.83%, respectively, under B0T2, B0T3, B1T1, B1T2, and B1T3. The root-shoot ratio of cucumber was 3.92%, 3.13%, 3.63%, 3.84%, 4.41%, and 3.82%, respectively, under the B0T1, B0T2, B0T3, B1T1, B1T2, and B1T3. Therefore, this study can provide a basis for the research on greenhouse environmental control and cucumber cultivation management. Keywords: greenhouse, cucumber, powdery mildew, nutrient solution, drought stress, growth traits, physiological traits DOI: 10.25165/j.ijabe.20221502.6838 Citation: Mao H P, Wang Y F, Yang N, Liu Y, Zhang X D. Effects of nutrient solution irrigation quantity and powdery mildew infection on the growth and physiological parameters of greenhouse cucumbers. Int J Agric & Biol Eng, 2022; 15(2): 68–74.